Mutations in cyclic AMP-dependent protein kinase and corticotropin (ACTH)-sensitive adenylate cyclase affect adrenal steroidogenesis. - Rae, P A (1979)
Two groups of mutant clones were isolated from YI adrenocortical tumor cells. One group, Y1(Kin), exhibited altered cytosolic cyclic AMP-dependent protein kinase activity; the second group, Y1(Cyc), exhibited diminished corticotropin-responsive adenylate cyclase activity. Steroidogenic responses to corticotropin and cyclic nucleotides closely paralleled cyclic AMP-dependent protein kinase activity in the Y1(Kin) mutants. In Y1(Cyc) mutants, corticotropin had little effect on steroidogenesis, whereas cyclic nucleotides were fully active. These data imply that adenylate cyclase and cyclic AMP-dependent protein kinase are obligatory components of the corticotropin-stimulated steroidogenic pathway.